Autism Spectrum Disorder Symptom Profile Across the RASopathies - Geoffray, Marie-Maude; Falissard, Bruno; Green, Jonathan; Kerr, Browyn; Evans, D. Gareth; Huson, Susan; Burkitt-Wright, Emma; Garg, Shruti (Frontiers in Psychiatry, 2021)
Dysregulation of the Ras MAPK signalling pathway is implicated in the pathogenesis of Autism Spectrum Disorder (ASD). The RASopathies, a group of disorders caused by mutations of the Ras/MAPK pathway genes share many overlapping clinical features. Studies suggest a high prevalence of ASD in the RASopathies but detailed characterization of the ASD profile is lacking. The aim of this study was to compare the ASD symptom profile of three distinct RASopathies associated with both gain of function and loss of function mutations: Neurofibromatosis type 1 (NF1), Noonan Syndrome (NS) and Cardio-facio-cutaneous syndrome (CFC). Participants were drawn from existing databases if they had a diagnosis of a Rasopathy, met the criteria for ASD and were able to communicate verbally. We compared the phenotypic profile of NF1+ASD (n=48), NS+ASD (n=11) and CFC+ASD (n=7) on the Autism Diagnostic Inventory (ADI-R) and the Autism Diagnostic Observation Schedule (ADOS). We found subtle but non-significant group differences with higher levels of social impairments and lower restricted repetitive behaviours in the NF1 group as compared to the NS and CFC groups. We observed group differences in developmental milestones with most severe delays in CFC, followed by NS and NF1. Our results suggest that despite developmental differences, the ASD profile remains relatively consistent across the three RASopathies. Though our results need confirmation in larger samples, they suggest the possibility that treatment and mechanistic insights developed in the context of one RASopathy may be generalizable to others and possibly to non-syndromic ASD associated with dysregulation of Ras/MAPK pathway genes.